Peningkatan Hasil Belajar Matematika Dengan Menggunakan Model Pembelajaran Team Assisted Individualization - Rusmiati, Rusmiati (JURNAL GLOBAL EDUKASI, 2021)
Abstract: This study aims to determine whether the implementation of Team Assisted Individualization (TAI) on the subject matter of opportunity can improve the activity and learning outcomes of students of class XI-3 SMP Negeri 1 Meranti. This study uses Classroom Action Research on Class XI-3 students even semester at SMP Negeri 1 Meranti academic year 2016/2017, with the number of 33 students. Data collection methods used are documents, observations, and evaluation tests. Based on the results of the research on the pre-cycle of learner activity on the first cycle of 63.63% and in the second cycle increased to 87.87%. Student learning outcomes have increased the average value of 73.33 with 63.63% classical completeness learning in cycle I, and in cycle II the average value of learners increased to 83.48 with the completeness of classical learning reached 96.96% From these two cycles it is clear that there is increasing activity of learners and learning outcomes after application of TAI learning model. Furthermore, teachers can be more creative in using the learning model in accordance with the purpose of learning. Keywords: pattern of numbers; Team Assisted Individualization  Abstrak: Penelitian ini bertujuan untuk mengetahui apakah penerapan Team Assisted Individualization (TAI) pada materi pokok peluang dapat meningkatkan keaktifan dan hasil belajar peserta didik kelas XI-3 SMP Negeri 1 Meranti. Penelitian ini menggunakan Penelitian Tindakan Kelas pada peserta didik kelas XI-3 semester genap di SMP Negeri 1 Meranti tahun pelajaran 2016/2017, dengan jumlah 33 peserta didik. Metode pengumpulan data yang digunakan adalah dokumen, observasi, dan tes evaluasi. Berdasarkan hasil penelitian pada pra siklus keaktifan peserta didik pada siklus I sebesar 63,63% dan pada siklus II meningkat menjadi 87.87%. Hasil belajar peserta didik mengalami peningkatan yaitu nilai rata-rata 73,33 dengan ketuntasan belajar klasikal 63,63% pada siklus I, dan pada siklus II rata-rata nilai peserta didik meningkat menjadi 83,48 dengan ketuntasan belajar klasikal mencapai 96,96% Dari dua siklus tersebut jelas bahwa ada peningkatan keaktifan peserta didik maupun hasil belajar setelah diterapkannya model pembelajaran TAI. Selanjutnya para guru dapat lebih berkreasi dalam menggunakan model pembelajaran yang sesuai dengan tujuan pembelajaran. Kata kunci: pola bilangan; Team Assisted Individualization